Permanent and transitory shocks in the presence of asymmetric error correction - Chan, Felix; MacDonald, Garry (Routledge, 2015)
This article highlights the potential importance of asymmetries in the loading vector of a set of cointegrated variables for the construction, analysis and interpretation of permanent and transitory shocks using impulse response functions. We derive an asymmetric version of the Permanent–Transitory decomposition suggested by Gonzalo and Ng (2001) and illustrate the potential importance of such asymmetries using the ‘cay’ data of Lettau and Ludvigson (2004).